Gender dimensions of health-related challenges among urban poor during COVID-19 pandemic in low-and middle-income countries: a systematic review and gap analysis - Krushna Chandra Sahoo; Sapna Negi; Pranab Mahapatra; Kajal Samantaray; Girish Chandra Dash; Shubhankar Dubey; Mili Roopchand Sahay; Rakesh Kumar Sahoo; Debdutta Bhattacharya; Banamber Sahoo; Subhada Prasad Pani; Mariam Otmani del Barrio; et al. (Frontiers Media S.A., 2023)
The COVID-19 pandemic has varying effects on men, women, and the transgender population. However, there is a paucity of systematic evidence on how gender and other social determinants of health during COVID-19 are affected in resource constraint urban settings. This review describes the gender dimensions of health-related challenges among the urban poor during COVID-19 in LMICs. We searched 11 scholarly online repositories including PubMed, Embase, Web of Science, CINAHL using the domain "slums," "COVID-19", "LMICs" and "gender identities." We used thematic framework analysis to synthesize qualitative data, and meta-analysis to determine the pooled prevalence. We registered in PROSPERO (CRD42020203783). We identified 6490 records, and 37 articles included. The studies reported stress among 74% women and 78% men, depression among 59% women and 62% men, and anxiety among 79% women and 63% men. Men had more stress than women during COVID-19; men are primarily responsible for household sustenance. Women had more anxiety than men, possibly because they are often the primary caregivers for children and the older population. While the severity varies according to gender identity, their vulnerability mostly related to their literacy and economy, highlighting the significance of including all social determinants in future primary studies.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/#recordDetails.